TRAINING TRANSLATORS: FROM GENERAL REQUIREMENTS TO PARTICULAR APPROACHES - Nataliya Sopylyuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
This article deals with some aspects of teaching translation. This question has not received much attention not only in Ukraine, but in Translation Studies as a whole. The present study illustrates how linguistic and cultural divergences between source and target texts complicate the process of translation. The paper also investigates the concept of translator's competence and emphasises the main professional skills of a good translator. The author analyses the most evident challenges of translation process, which are likely to provide a small clue for better teaching translation and provides some references to didactic approaches of the translation process, suggested by different authors. The article is composed of four main parts. The first part regards to the representation of the role of translator nowadays, as well as the complexity of the translation process. The second part briefly examines some translation difficulties, caused by linguistic and cultural differences between source and target texts. Linguistic and cultural divergences between French and Ukrainian texts are studied on the material of translation into Ukrainian "In search of a lost time" by M. Proust. The third part is a brief overview of translator's competence. The article states that translator's competence consists of different sub-competences, namely: linguistic, extra-linguistic, translation sub-competence and psycho-physiological one. The fourth part focuses on some approaches to translators' training. Methods and activities recommended by professionals engaged in the education of future translators are described.